Digital game based learning. Proceedings of the 4th International Symposium for Information Design, 2nd of June 2005 at Stuttgart Media University - Burmester, MichaelGerhard, DanielaThissen, Frank [Hrsg.] (KIT Scientific Publishing, 2006)
Digital games are a significant element in the digital media and information society. They influence the development of media technologies as well as interface design, online social interaction and new evaluation approaches.The Fourth Symposium for Information Design focused on the question of how game based learning environments can motivate and stimulate learners in different situations, and improve learning. It presented didactical and pedagogical issues, as well as actual examples and concrete applications.